A case of large uterine cystic adenomyosis outside the uterus after laparoscopic myomectomy: a case report and literature review - Wancheng Zhao; Chunmei Zhang (BMC Women's Health)
Abstract Background Uterine cystic adenomyosis is a rare form of focal adenomyosis that is primarily located within the myometrium. In this case report, we present a unique case of adult uterine cystic adenomyosis found outside the uterus following laparoscopic myomectomy. Case presentation The patient was a 36-year-old Chinese woman who had previously undergone laparoscopic surgery at our hospital to remove a 4 cm diameter diameter uterine fibroid six years prior. She returned to our hospital due to excessive menstruation and intermittent right lower abdominal pain for one year. Pelvic computed tomography revealed an endometriotic cyst on the right posterior side of the uterus seemingly connected to the uterine cavity. During surgery, we successfully removed a large well-defined cyst filled with typical chocolate-like fluid located outside the uterus with its root deeply embedded in the myometrium. Following surgery, we administered gonadotropin-releasing hormone analogs for six cycles without any observed recurrence. Conclusion This study describes an unusual occurrence of large adult uterine cystic adenomyosis located outside the uterus after laparoscopic myomectomy, potentially supporting the theory that endometrial injury invagination may be responsible for this condition.